Chemical safety using functionalized carbon nanomaterials: neutralization and detection of organophosphorus compounds - Fonsaca, Jéssica E. S.; Hostert, Leandro [UNESP]; Zarbin, Aldo J. G.; Orth, Elisa S. (Royal Society of Chemistry (RSC), 2024)
Organophosphorus compounds act as a double-edged sword as these can be both beneficial and threatening to human health. Although they are compounds naturally occurring, their overuse or irregular storage can lead to several health and environmental problems. This happens because organophosphorus compounds are the basis for a wide variety of pesticides and chemical warfare. Thus, detecting and destroying these compounds through sensitive, selective, and inexpensive ways is essential. Therefore, this review summarizes research studies on the usage of carbon nanomaterials (graphene and carbon nanotubes) for sensing and detoxifying organophosphates. In fact, carbon-based materials are designable platforms once they allow for the customization of their surfaces, targeted at producing unique structures with superior properties. Herein, we are especially interested in displaying the performance of these materials after being covalently modified by functional groups, which are recognized to lead to more stable and reproducible materials when compared to non-covalently modified ones. Furthermore, we describe the most important characteristics, advantages, and disadvantages of these functionalized materials and shed light on how promising this field is, especially, with combined features such as portability and low cost.